Induction of Paraptotic Cell Death in Breast Cancer Cells by a Novel Pyrazolo[3,4-h]quinoline Derivative through ROS Production and Endoplasmic Reticulum Stress - Phuong Linh Nguyen; Chang Hoon Lee; Heesoon Lee; Jungsook Cho (MDPI AG, 2022)
Chemotherapy has been a standard intervention for a variety of cancers to impede tumor growth, mainly by inducing apoptosis. However, development of resistance to this regimen has led to a growing interest and demand for drugs targeting alternative cell death modes, such as paraptosis. Here, we designed and synthesized a novel derivative of a pyrazolo[3,4-h]quinoline scaffold (YRL1091), evaluated its cytotoxic effect, and elucidated the underlying molecular mechanisms of cell death in MDA-MB-231 and MCF-7 breast cancer (BC) cells. We found that YRL1091 induced cytotoxicity in these cells with numerous cytoplasmic vacuoles, one of the distinct characteristics of paraptosis. YRL1091-treated BC cells displayed several other distinguishing features of paraptosis, excluding autophagy or apoptosis. Briefly, YRL1091-induced cell death was associated with upregulation of microtubule-associated protein 1 light chain 3B, downregulation of multifunctional adapter protein Alix, and activation of extracellular signal-regulated kinase 1/2 and c-Jun N-terminal kinase. Furthermore, the production of reactive oxygen species (ROS) and newly synthesized proteins were also observed, subsequently causing ubiquitinated protein accumulation and endoplasmic reticulum (ER) stress. Collectively, these results indicate that YRL1091 induces paraptosis in BC cells through ROS generation and ER stress. Therefore, YRL1091 can serve as a potential candidate for the development of a novel anticancer drug triggering paraptosis, which may provide benefit for the treatment of cancers resistant to conventional chemotherapy.